Fish Preservation Industry Management Training in the Coastal Area of Ambon Island - Abednego, Abednego (Unram Journal of Community Service, 2025)
The background of the fish preservation industry management training is that the fish preservation industry managers in the coastal areas of Ambon Island have not yet fully implemented good business management. The purpose of this community service is to increase the capacity of human resources for industry managers to have managerial competencies. The focus of the training is all activities to provide, obtain, improve, and develop managerial competencies. The activities are carried out in several stages, namely: (1) Situational analysis of the management of the fish preservation industry is carried out to determine steps for identifying needs; (2) The activity planning stage includes the preparation of a syllabus and activity schedule; (3) the training implementation stage is carried out in 2 sessions, namely the first session providing material, in the form of information about managerial competencies and the second session in the form of group discussions; (4) sustainability plans: business development and ongoing mentoring. This community service activity has succeeded in increasing managerial abilities and skills among fish preservation industry managers. The impact felt is increased self-confidence in doing business.